2017
DOI: 10.1038/s41598-017-15823-6
|View full text |Cite
|
Sign up to set email alerts
|

DNA metabarcoding for high-throughput monitoring of estuarine macrobenthic communities

Abstract: Morphology-based profiling of benthic communities has been extensively applied to aquatic ecosystems’ health assessment. However, it remains a low-throughput, and sometimes ambiguous, procedure. Despite DNA metabarcoding has been applied to marine benthos, a comprehensive approach providing species-level identifications for estuarine macrobenthos is still lacking. Here we report a combination of experimental and field studies to assess the aptitude of COI metabarcoding to provide robust species-level identific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 59 publications
(75 reference statements)
4
94
2
Order By: Relevance
“…Metabarcoding offers a rapid, high-resolution, cost-effective approach to biodiversity assessment, where entire communities can be identified using High-Throughput Sequencing (HTS) in conjunction with community DNA from bulk tissue samples (DNA metabarcoding), or environmental DNA (eDNA) from environmental samples (eDNA metabarcoding), such as soil or water (Deiner et al, 2017;Taberlet, Coissac, Pompanon, Brochmann, & Willerslev, 2012). DNA metabarcoding of aquatic invertebrate samples has proven relatively successful, with applications in biomonitoring (Andújar et al, 2017;Elbrecht, Vamos, Meissner, Aroviita, & Leese, 2017a;Emilson et al, 2017;Lobo, Shokralla, Costa, Hajibabaei, & Costa, 2017). Use of eDNA metabarcoding for invertebrate assessment in freshwater rivers (Blackman et al, 2017;Carew, Kellar, Pettigrove, & Hoffmann, 2018;Deiner, Fronhofer, Mächler, Walser, & Altermatt, 2016;Klymus, Marshall, & Stepien, 2017;Leese et al, 2020), streams (Macher et al, 2018), and lakes (Klymus et al, 2017) is also gaining traction, but there are currently few published studies that have used metabarcoding for small lake or pond invertebrates (Beentjes, Speksnijder, Schilthuizen, Hoogeveen, & van der Hoorn, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabarcoding offers a rapid, high-resolution, cost-effective approach to biodiversity assessment, where entire communities can be identified using High-Throughput Sequencing (HTS) in conjunction with community DNA from bulk tissue samples (DNA metabarcoding), or environmental DNA (eDNA) from environmental samples (eDNA metabarcoding), such as soil or water (Deiner et al, 2017;Taberlet, Coissac, Pompanon, Brochmann, & Willerslev, 2012). DNA metabarcoding of aquatic invertebrate samples has proven relatively successful, with applications in biomonitoring (Andújar et al, 2017;Elbrecht, Vamos, Meissner, Aroviita, & Leese, 2017a;Emilson et al, 2017;Lobo, Shokralla, Costa, Hajibabaei, & Costa, 2017). Use of eDNA metabarcoding for invertebrate assessment in freshwater rivers (Blackman et al, 2017;Carew, Kellar, Pettigrove, & Hoffmann, 2018;Deiner, Fronhofer, Mächler, Walser, & Altermatt, 2016;Klymus, Marshall, & Stepien, 2017;Leese et al, 2020), streams (Macher et al, 2018), and lakes (Klymus et al, 2017) is also gaining traction, but there are currently few published studies that have used metabarcoding for small lake or pond invertebrates (Beentjes, Speksnijder, Schilthuizen, Hoogeveen, & van der Hoorn, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…2) DNA and eDNA metabarcoding would enable species resolution data for problematic taxa that cannot be morphotaxonomically identified to species-level using standard keys (e.g. Blackman et al, 2017;Elbrecht et al, 2017a;Lobo et al, 2017;Nichols et al, 2020); and 3) alpha diversity would be lower in ponds with crucian carp due to direct predation or altered habitat quality (e.g. Lemmens et al, 2013;Maceda-Veiga, López, & Green, 2017;Schilling et al, 2009a;Wood et al, 2001), but beta diversity would be enhanced due to community heterogeneity induced by crucian carp presence in the pond network (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…(1) Bulk DNA metabarcoding of macroinvertebrates has proven successful in several studies so far (Hajibabaei et al 2012;Yu et al 2012;Ji et al 2013;Gibson et al 2014Gibson et al , 2015Elbrecht et al 2017a;Emilson et al 2017;Lobo et al 2017) and is even applicable to bioassessment in freshwater and marine environments alike (Aylagas et al 2014(Aylagas et al , 2018Elbrecht et al 2017a). However, the most obvious technical challenges with bulk sample analysis are processing speed (i.e.…”
Section: Consensusmentioning
confidence: 99%
“…Both primer combinations have been previously found to perform better across metazoan phylogenetic diversity than the mICOIintF reverse complement with LCO1490 (and its degenerate versions dgLCO1490 and jgLCO1490) (Leray et al 2013). A primer pair targeting exactly this same region, but using instead LoboR1 (Lobo et al 2013(Lobo et al , 2017 has been shown to produce similar or higher taxa recovery (e.g. Haenel et al 2017, Ip et al 2019, Chang et al 2020, but it has not been tested yet in NIS-focused studies.…”
Section: Marker Loci and Primer Pairsmentioning
confidence: 99%